Institutional open access at home and outward internationalization - Sun, S.; Peng, Mike; Lee, R.; Tan, W. (Pergamon, 2015)
While voluminous research has focused on the impact of host country institutions on foreign entrants, the rise of outward internationalization of firms from emerging economies is challenging this research stream. Limited work has been done to investigate a crucial question: How do home country institutions influence firms from emerging economies to engage in outward internationalization? Inspired by North's insights on institutional open access, we develop an institution-based framework highlighting intra-country (sub-national) regional differences within a large emerging economy. Specifically, we argue that greater institutional open access in a particular region of a home country-in the areas of legal environment openness and financial market openness-leads to greater outward internationalization of local firms headquartered in that region. Further, tenure of that region's governor moderates such relationships in different ways. Our multilevel analysis with 5239 observations (company-years) finds that institutional open access is indeed behind some Chinese firms' outward internationalization.